PENGOLAHAN ARSIP STATIS DI SUB DIREKTORAT PENGOLAHAN ARSIP KONVENSIONAL SETELAH TAHUN 1945 ANRI - , GANDIS GAYATRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The writing of graduating paper entitled âThe Processing of Archives in Sub Direktorat Pengolahan Arsip Konvensional Setelah Tahun 1945 ANRIâ is a result of data collection Field Work Practices which was done at ANRI. The purpose of this Field Work Practices is to determine the processing of conventional archives. Scope of the problem are suporting tools of the archives processing activities, the problems occured in the processing, and the solution of the problems. The methods used in the study, including direct interview, observation , and library research. The purpose of the interview is to compelete imperfect datas and get the detail information from the original speakers which are the experts of their field. The implementation of the Job Practice, was held direct observation of the archives processing in the ANRI to get the primary data which are valid and can be trusted and related to the whole object. The conclusion of this graduating paper is that the archival processing in ANRI is done optimally. It is proved by the implemented system that its quality standard has been awarded and implemented according to the regulations.